Interventional Treatment of Labial Varices - Risner, Victoria; McColgan, Yuko; Salazar, Gloria (Seminars in Interventional Radiology, 2023)
Labial varices are commonly seen in women with varicose veins of the pelvis. Initial management is conservative management since labial varies typically resolve, particularly in pregnant patients following delivery. Varices can be seen also in association with pelvic varices in the pelvic venous disease spectrum. Sclerotherapy is often the management. This article reviews the presentation and treatment of patients with labial varices, with a focus on interventional radiologic management.
Keywords: interventional radiology; varices; labial; vulvar; sclerotherapy; pelvic venous disorder